Temperature Effect on ON/OFF Current Ratio of FinFET Transistor - Hashim, Yasir (IEEE, 2017)
This paper demonstrates the working temperature effect on ON/OFF current ratio of FinFET transistor and the prospect of using it as a temperature nano-sensor. The characteristics of the FinFET transistors were simulated using MUGFET simulation tool at different working temperature. Output characteristics with a working temperature range (-25oC to 125oC) were simulated. Variation of ON current to OFF current ratio (Ion/Ioff) with working temperature was investigated.